Identificación de ácaros fitófagos y predadores asociados al cultivo de pitahaya (Selenicereus megalanthus) - Saca Poma, Jeison Damian (2023)
Phytophagous mites are a very important economic factor to consider because they cause decrease and losses of 20 - 30% in some regions of the country. Affecting the economic income of producers directly. These organisms attack the crop giving various types of symptoms, even affecting the fruits of the crop and preventing them from going to the international market due to their physical characteristics. For this reason, the following investigation was proposed with the objective of: determining the acarina fauna associated with the cultivation of yellow dragon fruit in the canton El Pangui. The identification of the various types of mites was carried out at the Technical University of Ambato in the entomology laboratories of said University. Only one genre of phytophagous mite was found: Tydeus, while the predatory genera were the ones found in the greatest number: Tarsonemus, Oribatida morfotipo 1, Oribatida morfotipo 2 and Ambliseus. The high percentage of predators may explain the low presence of phytophagous genera. Keywords: Tydeus, Oribatida, acarina population.